Focal and diffuse cervical spinal cord damage in patients with early relapsing–remitting MS: A multicentre magnetisation transfer ratio study. (July 2019) - Combès, Benoît; Kerbrat, Anne; Ferré, Jean Christophe; Callot, Virginie; Maranzano, Josefina; Badji, Atef; Le Page, Emmanuelle; Labauge, Pierre; Ayrignac, Xavier; Carra Dallière, Clarisse; de Champfleur, Nicolas Menjot; Pelletier, Jean; et al.
Background: Studies including patients with well-established multiple sclerosis (MS) have shown a significant and disability-related reduction in the cervical spinal cord (SC) magnetisation transfer ratio (MTR). Objectives: The objectives are to (1) assess whether MTR reduction is already measurable in the SC of patients with early relapsing–remitting multiple sclerosis (RRMS) and (2) describe its spatial distribution. Methods: We included 60 patients with RRMS <12  months and 34 age-matched controls at five centres. Axial T2*w, sagittal T2w, sagittal phase-sensitive inversion recovery (PSIR), 3DT1w, and axial magnetisation transfer (MT) images were acquired from C1 to C7. Lesions were manually labelled and mean MTR values computed both for the whole SC and for normal-appearing SC in different regions of interest. Results: Mean whole SC MTR was significantly lower in patients than controls (33.7 vs 34.9  pu, p   =  0.00005), even after excluding lesions (33.9  pu, p   =  0.0003). We observed a greater mean reduction in MTR for vertebral levels displaying the highest lesion loads (C2–C4). In the axial plane, we observed a greater mean MTR reduction at the SC periphery and barycentre. Conclusion: Cervical SC tissue damage measured using MTR is not restricted to macroscopic lesions in patients with early RRMS and is not homogeneously distributed.